Analysis of Factors Influencing Purchasing Decisions at Ayesha Cell Kedungpring - Faris Dwi Febrianto; Abid Muhtarom; Titin Titin (Jurnal Price : Ekonomi dan Akuntasi, 2024)
This study aims to analyze the influence of brand image, product quality, and price perception on consumer purchase decisions at Ayesha Cell Kedungpring. The study used a quantitative approach with primary data collected through questionnaires to 94 respondents who were consumers of Ayesha Cell Kedungpring. Data were analyzed using IBM SPSS Statistics 26 through validity test, reliability test, classical assumption test, multiple linear regression, determination coefficient, t-test, and F-test. Product quality also had a positive and significant effect with t count 5.362 and significance 0.000, while price perception had a positive and significant effect with t count 4.409 and significance 0.000. Simultaneously, brand image, product quality, and price perception have a significant effect on purchasing decisions with F count 91.563 greater than F table 2.706. An R-Square value of 0.753 indicates that 75.3% of the variation in purchasing decisions can be explained by all three variables, while 24.7% is explained by other variables outside the model. The most dominant variable was the brand image with the highest regression coefficient of 0.654.